2021
DOI: 10.15835/nbha49212349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some DNA extraction methods from monovarietal must and wines

Abstract: The methods applied for DNA extraction from must and wine samples with monovarietal origin are presented and discussed aiming to prove the quality of extracted DNA and its good properties for further use in molecular tests. In the present research were compared four different DNA extraction methods from must and wine samples obtained from eleven V. vinifera varieties (five grapevine varieties for white wines and six grapevine varieties for red wines, respectively). Taking into consideration the amounts of obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…12 The main limitations of such analysis are related to the complexity of the vegetable sample, the loss of DNA integrity throughout food processing, 13 the risk of crosscontamination during various steps of DNA analysis, 14 and the presence of compounds that prevent DNA detection, such as PCR inhibitors. 15 Therefore, efficient DNA extraction and purification are crucial for the success of DNA-based methods. 15 Likewise, there is increasing interest in fast and reliable methods with high sensitivity and multiplexing possibilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The main limitations of such analysis are related to the complexity of the vegetable sample, the loss of DNA integrity throughout food processing, 13 the risk of crosscontamination during various steps of DNA analysis, 14 and the presence of compounds that prevent DNA detection, such as PCR inhibitors. 15 Therefore, efficient DNA extraction and purification are crucial for the success of DNA-based methods. 15 Likewise, there is increasing interest in fast and reliable methods with high sensitivity and multiplexing possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, efficient DNA extraction and purification are crucial for the success of DNA-based methods. 15 Likewise, there is increasing interest in fast and reliable methods with high sensitivity and multiplexing possibilities. 16 In this sense, micro-total analysis systems (μTASs), also known as lab-on-a-chip, aim to completely integrate multiple laboratory processes in a single miniaturized platform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pereira et al, 2011, reported a DNA wine extraction method starting with a 10 mL sample that resulted in a 3 ng DNA yield by 2-propanol precipitation, enzyme treatment, phenol and chloroform extraction, and several washes . Onache et al, 2021, showed the efficiency of DNA yield from different wine samples ranging from 18 to 85 ng/μL using Qiagen DNeasy Plant Kit . It should be taken into account that not all reportedly successful methods could be applied to any wine samples.…”
mentioning
confidence: 99%
“… 25 Onache et al, 2021, showed the efficiency of DNA yield from different wine samples ranging from 18 to 85 ng/μL using Qiagen DNeasy Plant Kit. 26 It should be taken into account that not all reportedly successful methods could be applied to any wine samples. DNA amplification is frequently performed for the enrichment of the total DNA of a particular species by the use of universal primers for such species.…”
mentioning
confidence: 99%